TOURISM CARRYING CAPACITY OF SEJANGAN ISLAND BEACH, LABUHAN TERATA, LABUHAN KURIS VILLAGE, SUMBAWA REGENCY, WEST NUSA TENGGARA - Hendra Saputra; Syamsul Bahri; Yudi Ahdiansyah (Universitas Mataram, 2025)
This study aims to: (1) analyze the suitability of the area for beach recreation tourism activities and its tourism carrying capacity, and (2) estimate the area's carrying capacity for beach recreation tourism activities. The research was conducted from June to August 2021 on Sejangan Island, Labuhan Terata Hamlet, Labuhan Kuris Village. An exploratory method was employed, utilizing a survey and direct field measurements. Data comprised primary data, obtained directly from the field in the form of measurement estimates, surveys, observations, and interviews with tourists and relevant stakeholders, as well as secondary data gathered from literature studies and documents from related institutions. The results indicate that the tourism suitability of Sejangan Island for beach recreation is as follows: zones 2, 3, 4, and 5 fall into the highly suitable (S1) category at 90%, 94.44%, 93.33%, and 85.56%, respectively, while zone 1 is categorized as suitable (S2) at 73.33%.